Lenalidomide-Related Spinal Cord Infarction in Primary Amyloidosis - Makranz, Chen; Nachmias, Boaz; Gatt, Moshe E.; Eliahou, Ruth; Lossos, Alexander (Archives of Clinical and Medical Case Reports, 2018)
Spinal cord infarction is a rare but often devastating disorder caused by disruption in the vascular spinal supply. We report a patient with spinal cord infarction associated with lenalidomide therapy for primary amyloidosis, in the background of other predisposing factors. We describe the clinical case and discuss the possible explanation for this rare complication. As spinal cord infarction is not a known complication of lenalidomide therapy or amyloidosis, this description raises the potential of such a side effect in some certain conditions and discusses the role of the old and new anticoagulant agents in prevention of thromboembolic complications in high-risk patients.